RANCANGAN PEMBELAJARAN BERBASIS PENDEKATAN REALISTIC MATHEMATIC EDUCATION (RME) UNTUK MENGEMBANGKAN KEMAMPUAN REPRESENTASI MATEMATIS SISWA KELAS IV SEKOLAH DASAR - Dwi Safitri, - (2021)
This research is aims to develop mathematical representation ability in 4th grade students at Bandung City. This study used qualitative approach methods by Delphi. The instruments of this study use an assessment sheet in order to lesson plan based on Realistic Mathematic Education (RME) approach in 4th grade students by a education expert. The final result is that the experts agree that the learning design based on the Realistic Mathematical Education (RME) approach can develop mathematical representation abilities in 4th grade elementary school students. This includes all the components in this learning design, namely the Learning Implementation Plan (RPP), teaching materials, Student Worksheets (LKPD), learning media, and learning assessments that are in accordance with the Realistic Mathematical Education (RME) approach and can develop skills representation of grade 4 elementary school students.